Allosteric Modulator Leads Hiding in Plain Site: Developing Peptide and Peptidomimetics as GPCR Allosteric Modulators - Olson, Keith M.; Traynor, John R.; Alt, Andrew (Frontiers in Chemistry, 2021)
Allosteric modulators (AMs) of G-protein Coupled Receptors (GPCRs) are desirable drug targets because they can have fewer on-target side effects, improved selectivity, and more precise control over signaling (e.g., biased signaling) than orthosteric drugs. An underappreciated source for identifying AMs are peptides and proteins – many of which were evolutionarily selected as AMs – derived from endogenous protein-protein interactions (e.g., transducer/accessory proteins), intramolecular receptor contacts (e.g., pepducins or extracellular domains), endogenous peptides, and exogenous sources (e.g., nanobodies, or conotoxins). Peptides offer distinct advantages over small molecules, including high affinity, good tolerability, good bioactivity, and modular/automatable synthesis; but specific disadvantages, including poor metabolic stability and pharmacokinetics. Peptidomimetics – small molecules derived from peptides or peptide modifications improving stability and bioavailability – address these limitations by retaining the high affinity and high potency peptide pharmacophore while improving druggability. This review aims to: 1) demonstrate that peptides and peptidomimetics are underexploited in AM drug discovery; 2) review peptidomimetic AMs and design strategies; and 3) critically analyze the advantages, disadvantages, and future directions of peptidomimetic AMs. While small molecules will and should play a vital role in AM drug discovery, peptidomimetics can complement and even exceed the advantages of small molecules, depending on the target, site, lead, etc.